1998
DOI: 10.1088/0031-9155/43/10/005
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of depth dose and dose per monitor unit for irregularly shaped electron fields

Abstract: A new dosimetric quantity, the lateral build-up ratio (LBR), has been introduced to calculate depth dose distribution for any shaped field. Factors to account for change in incident fluence with collimation are applied separately. The LBR data for a small circular field are used to extract radial spread of the pencil beam, sigma(r), as a function of depth and energy. By using the relationship between LBR, sigma(r), energy and depth, a formalism is developed to calculate dose per monitor unit for any shaped fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 15 publications
6
86
0
Order By: Relevance
“…A second method of determining the dose output is through the use of an analytical algorithm, such as the method described by Khan et al, 42,43 or a Monte Carlo code. An example of the latter is given by Kapur et al 44 These types of systems are not in widespread clinical use, but may become more prevalent in the future.…”
Section: B2 Field-size Determinationmentioning
confidence: 99%
“…A second method of determining the dose output is through the use of an analytical algorithm, such as the method described by Khan et al, 42,43 or a Monte Carlo code. An example of the latter is given by Kapur et al 44 These types of systems are not in widespread clinical use, but may become more prevalent in the future.…”
Section: B2 Field-size Determinationmentioning
confidence: 99%
“…The sector integration concept [4,5,21], which is similar to Clarkson's model for calculation of the output factor for photon beams [22], has also been reported with accurate prediction of ROF. Even though we have not verified, sector integration similar to Khan et al [9] could be used with our equation and will be reported in a separate study.…”
Section: Cone Sizesmentioning
confidence: 92%
“…The ROF of circular fields are investigated in this study. Khan et al [9] reported a method for predicting ROF with irregular field using lateral build-up ratio concept. The sector integration concept [4,5,21], which is similar to Clarkson's model for calculation of the output factor for photon beams [22], has also been reported with accurate prediction of ROF.…”
Section: Cone Sizesmentioning
confidence: 99%
“…The dose calculation algorithms adapted by commercial electron treatment planning systems are the pencil beam method1, 2 and the Monte Carlo simulation method 3, 4, 5. The CadPlan TPS (Varian Medical Systems Inc., Palo Alto, CA, USA) uses a generalized Gaussian pencil beam model to calculate electron dose.…”
Section: Introductionmentioning
confidence: 99%